2011
DOI: 10.3144/expresspolymlett.2011.87
|View full text |Cite
|
Sign up to set email alerts
|

Study of matrix micro-cracking in nano clay and acrylic tri-block-copolymer modified epoxy/basalt fiber-reinforced pressure-retaining structures

Abstract: Abstract. In fiber-reinforced polymer pressure-retaining structures, such as pipes and vessels, micro-level failure commonly causes fluid permeation due to matrix cracking. This study explores the effect of nano-reinforcements on matrix cracking in filament-wound basalt fiber/epoxy composite structures. The microstructure and mechanical properties of bulk epoxy nanocomposites and hybrid fiber-reinforced composite pipes modified with acrylic tri-block-copolymer and organophilic layered silicate clay were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
0
12
0
1
Order By: Relevance
“…In these systems, the fracture toughness can be increased by forming multiphase morphology with the ability to initiate various toughening mechanisms during crack growth (Bashar, Sundararaj, & Mertiny, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In these systems, the fracture toughness can be increased by forming multiphase morphology with the ability to initiate various toughening mechanisms during crack growth (Bashar, Sundararaj, & Mertiny, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Though, epoxies are used as insulators in electrical machineries, switchgears and transformers [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that nanostructured block-copolymers can be an attractive alternative to the conventional micro-particles. Self-assembling amphiphilic block-copolymers provide a highly efficient way of improving epoxy toughness with a relatively low amount of additive loading [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Typically, block-copolymers are distinct and chemically dissimilar polymer blocks linked together by covalent bonds.…”
Section: Introductionmentioning
confidence: 99%